Invisible detergents for structure determination of membrane proteins by small‐angle neutron scattering. (30th December 2017) - Midtgaard, Søren Roi; Darwish, Tamim A.; Pedersen, Martin Cramer; Huda, Pie; Larsen, Andreas Haahr; Jensen, Grethe Vestergaard; Kynde, Søren Andreas Røssell; Skar‐Gislinge, Nicholas; Nielsen, Agnieszka Janina Zygadlo; Olesen, Claus; Blaise, Mickael; Dorosz, Jerzy Józef; et al.
Abstract : A novel and generally applicable method for determining structures of membrane proteins in solution via small‐angle neutron scattering (SANS) is presented. Common detergents for solubilizing membrane proteins were synthesized in isotope‐substituted versions for utilizing the intrinsic neutron scattering length difference between hydrogen and deuterium. Individual hydrogen/deuterium levels of the detergent head and tail groups were achieved such that the formed micelles became effectively invisible in heavy water (D2 O) when investigated by neutrons. This way, only the signal from the membrane protein remained in the SANS data. We demonstrate that the method is not only generally applicable on five very different membrane proteins but also reveals subtle structural details about the sarco/endoplasmatic reticulum Ca 2+ ATPase (SERCA). In all, the synthesis of isotope‐substituted detergents makes solution structure determination of membrane proteins by SANS and subsequent data analysis available to nonspecialists. Abstract : A generally applicable method for determining structures of membrane proteins in solution via small‐angle neutron scattering (SANS) is presented. Common detergents for solubilizing membrane proteins were synthesized in isotope‐substituted versions such that they became effectively invisible in heavy water (D2 O) when investigated by neutrons. We demonstrate that this method is generally applicable and makes solution structure determination of membrane proteins by SANS and subsequent data analysis available to nonspecialists.